hdiemht

Cựu Mod Toán
Thành viên
11 Tháng ba 2018
1,813
4,022
481
18
Quảng Trị
$Loading....$
[tex]\left\{\begin{matrix} x^{3}y+xy-x-5=0\\ x^{6}y^{2}-x^{2}y^{2}+2x^{2}y-x^{2}=5 \end{matrix}\right.[/tex]
[tex]\left\{\begin{matrix} x^{3}y+xy-x-5=0\\ x^{6}y^{2}-x^{2}y^{2}+2x^{2}y-x^{2}=5 \end{matrix}\right.\Leftrightarrow \left\{\begin{matrix} x^3y+(xy-x)=5 & & \\ (x^3y)^2-(xy-x)^2=5 & & \end{matrix}\right.[/tex]
Đặt: [tex]x^3y=a;(xy-x)=b[/tex]
Khi đó ta có: [tex]\left\{\begin{matrix} a+b=5 & & \\ a^2-b^2=5 & & \end{matrix}\right.\Leftrightarrow \left\{\begin{matrix} a+b=5 & & \\ a-b=1 & & \end{matrix}\right.\Leftrightarrow \left\{\begin{matrix} a=3 & & \\ b=2 & & \end{matrix}\right.[/tex]
Từ đó dễ dàng suy ra: $x;y$ nhé!
 
Top Bottom